MECHANISM OF MIR-25-3P CARRIED BY EXTRACELLULAR VESICLES DERIVED FROM PLATELET-RICH PLASMA IN IL-1β–INDUCED NUCLEUS PULPOSUS CELL DEGENERATION VIA THE SOX4/CXCR7 AXIS. Issue 1 (19th July 2022) - Hu, Baoshan; Wang, Lianxin; Sun, Naikun; Lin, Shengrong; Rui, Gang
ABSTRACT: Objectives: Nucleus pulposus (NP) cell degeneration promotes the progression of intervertebral disc (IVD) degeneration. MicroRNAs (miRs) are associated with IVD degeneration. This study expounded the mechanism of microRNA (miR)-25-3p carried by extracellular vesicles (EVs) derived from platelet-rich plasma (PRP) in interleukin (IL)-1β–induced NP cell degeneration. Methods: Platelet-rich plasma from mouse blood was obtained, and EVs were isolated from PRP (EVs derived from PRP [PRP-EVs]) and identified. Nucleus pulposus cells were isolated from the mouse lumbar IVD and treated with IL-1β to induce NP cell degeneration. Extracellular vesicles derived from PRP were added into NP cell culture medium. Afterward, intracellular miR-25-3p, sex determining region Y-related high-mobility-group box 4 (SOX4), and CXC chemokine receptor 7 (CXCR7) levels were examined. Nucleus pulposus cell viability, apoptosis, and inflammation were detected. Extracellular vesicles derived from PRP were labeled by PKH67 to obverse the uptake of EVs by NP cells. The binding relations between SOX4 and miR-25-3p and CXCR7 were predicted and examined. Functional rescue experiments were performed to investigate the roles of miR-25-3p, SOX4, and CXCR7 in NP cell degeneration. Results: miR-25-3p was downregulated, whereas SOX4 and CXCR7 were upregulated in IL-1β–induced NP cells. Extracellular vesicles derived from PRP increased the cell viability, and decreased apoptosis and inflammation. miR-25-3p carried by PRP-EVs into NP cells alleviated NP cell degeneration. miR-25-3p inhibited SOX4 expression and limited CXCR7 transcription. Silencing miR-25-3p or overexpressing SOX4 or CXCR7 reversed the alleviating role of PRP-EVs in NP cell degeneration. Conclusion: miR-25-3p carried by PRP-EVs into NP cells elevated intracellular miR-25-3p expression, which suppressed SOX4 expression and further limited CXCR7 transcription, thus alleviating IL-1β–induced NP cell degeneration. Extracellular vesicles derived from PRP containing miR-25-3p may be a new method for IVD treatment.